The last camellia : a novel - Jio, Sarah (Plume, 2013)
"On the eve of the Second World War, the last surviving specimen of a camellia plant known as the Middlebury Pink lies secreted away on an English country estate. Flora, an amateur American botanist, is contracted by an international ring of flower thieves to infiltrate the household and acquire the coveted bloom. Her search is at once brightened by new love and threatened by her discovery of a series of ghastly crimes. More than half a century later, garden designer Addison takes up residence at the manor, now owned by the family of her husband, Rex. The couple's shared passion for mysteries is fueled by the enchanting camellia orchard and an old gardener's notebook. Yet its pages hint at dark acts ingeniously concealed. If the danger that Flora once faced remains very much alive, will Addison share her fate?" -- from author's web page.